Pengembangan Metode PCR Multipleks untuk Analisis Genotipe Null Gen GSTM1/GSTT1 pada Pasien Tuberkulosis - Prayuni, Kinasih; Razari, Intan; Nihayah, Silviatun; Syafrizal; Yuliwulandari, Rika (Puslitbang Sinergis Asa Professional, 2023)
Tuberculosis (TB) remains Indonesia's leading infectious disease. Hepatotoxicity is the most common side effect of TB first-line medication therapy in TB patients. GSTM1 and GSTT1 are glutathione S-transferase (GST) genes involved in the detoxification of various toxic compounds such as drugs. The development of fast and simple methods for null genotyping of GSTM1/GSTT1 could facilitate large pharmacogenetic studies and the clinical application of personalized drug dose adjustment according to the patient's genetic profile. The aim of this research was to develop a multiple PCR method for simultaneous amplification of GSTM1/GSTT1 genes for molecular analysis. A total of 25 samples of TB patients were used to validate the method consisting of TB patients with hepatotoxicity and without hepatotoxicity. Our result showed the genotype frequency of the GSTM1 null genotype was 90% in TB patients with hepatotoxicity and 100% in TB patients without hepatotoxicity. The frequency of the GSTT1 null genotype in TB patients with hepatotoxicity was 90%, whereas in TB patients without hepatotoxicity was 80%. The sequencing results on the positive samples showed a similarity of 99% to the GenBank NCBI. Our study was successful in detecting GSTM1 and GSTT1 null genotypes using the multiplex PCR method in TB patients. Further study needs to be done with larger sample of TB patients.